ANALISIS PENGGUNAAN MEDIA LAGU DALAM MENINGKATKAN MINAT BELAJAR DAN DAYA INGAT SISWA SEKOLAH DASAR - Pramesti, Erlintang; Khofifah, Ayu Dewi Nafisatul; Shallum, Geitsya Alodia; Wijayanto, Wasis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of song media in increasing learning interest and memory of elementary school students, especially in grades III and IV. The background of this study is based on the problem of low student learning interest caused by monotonous teaching methods and the minimal use of interesting learning media. This study uses a descriptive qualitative approach with data collection techniques in the form of observation and documentation, which is strengthened by a literature review from various relevant scientific sources. Data are analyzed through the stages of data reduction, information presentation, and conclusion drawing. The results of the study indicate that the use of song media, such as the song